Efficacy and Safety of a Self-Improved Continuous Bladder Irrigation Sensor Device in Patients after Transurethral Resection of the Prostate: A Prospective Study - Tao, Rong-zhen; Li, Ai; Su, Shu; Tang, Qing-lai; Mao, Juan-juan; Zhou, Shuang (Urology Journal, 2024)
Purpose: To explore the efficacy and safety of a self-improved continuous bladder irrigation (CBI) sensor device after transurethral resection of the prostate (TURP). Materials and Methods: A total of 160 patients with benign prostatic hyperplasia who received TURP from June 2021 to May 2022 were selected. According to the envelope randomization method, patients were divided into a control group (80 cases) and study group (80 cases). In the control group, the speed of bladder flushing fluid was adjusted according to the clinical experience of nurses. On the basis of the control group, the self-improved CBI sensor device was used in the study group to observe the postoperative comfort and complication rate in the two groups. Results: The comfort of patients in the study group was significantly higher than that of patients in the control group (97.50% vs. 88.75%, P = .023), and the number of postoperative complications in the control group was significantly higher than that in the study group (8.75% vs. 1.25%, P = .021). Meanwhile, the average amount of irrigation fluid in the study group was obviously lower than that in the control group (26.4 L vs. 27.8 L, P = .011). In addition, patients in the study group had a significantly shorter hospital stay than the controls (3.3 days vs. 3.6 days, P = .005). Conclusion: Implementation of the new self-improved CBI sensor device for patients after TURP can improve their awareness regarding disease-related knowledge, alleviate their fear and anxiety, improve their compliance and comfort with treatment and nursing, and reduce the incidence of complications.